Rethinking Hijab in Contemporary Indonesia: A Study of Hijab Community “Tuneeca Lover Community” - Wardah Nuroniyah (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2019)
Hijab (veil) for female Muslims has been subject to a debate regarding its meanings. On the one hand, it represents the virtue of religious obedience and piety. Still, on the other hand, it is associated with the form of women oppressions in the public domain. At this point, the hijab has been an arena of contesting interpretations. Meanwhile, contemporary Indonesia is witnessing the increase in the use of veil among urban female Muslims that leads to the birth of various hijab wearer communities. One of them is Tuneeca Lover Community (TLC). This community has become a new sphere where female Muslims articulate their ideas about Islam through various activities such as religious gathering, hijab tutorial class, fashion show, and charity activities. This study seeks to answer several questions: Why do these women decide to wear a hijab? Why do they join the TLC? How do they perceive the veil? Is it related to religious doctrines or other factors such as lifestyle? This research employs a qualitative method using documentation and interview to gather the data among 150 members of the TLC.  This research shows that their understanding of the hijab results from the common perception that places the veil as a religious obligation. Nevertheless, each of the members has one's orientation over the hijab. This paper also suggests that they try to transform this understanding into modern settings. As a consequence, they are not only committed to the traditionally spiritual meaning of the hijab but are also nuanced with modern ideas such as lifestyle and particular social class. Their participation in the TLC enables them to reach both goals simultaneously.